Foreign Direct Investment and Employment Creation in Pacific Island Countries: An Empirical Study of Fiji - T.K. Jayaraman; Baljeet Singh (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2007)
This paper undertakes an econometric study of the impact of FDI in Fiji during a 30-year period. In the absence of data on Fiji's employment in FDI sectors either in aggregated form or by specific sectors, we are constrained to use data on formal sector employment as a proxy. This implies that employment in both formal and FDI related activities move in the same direction and proportion. The paper investigated the relationship between employment and foreign direct investment for Fiji through a multivariate modeling strategy by including GDP.
Keywords: F1; 330; Foreign Direcit Investment; Employment creation; Fiji